Potensi Serbuk Daun Kelor (Moringa oleifera) Sebagai Anthelmintik Terhadap Infeksi Ascaris suum dan Feed Supplement pada Babi - Syukron, Muhammad Ulqiya; Damriyasa, I Made; Suratma, Nyoman Adi (Veterinary Science and Medicine Journal, 2014)
Pig ascariasis is an intestinal parasitic disease caused by Ascaris suum. The economic losses in pig ascariasis are caused by a bad feed conversion ratio (FCR) and rejection of some organs after animal slaughtering. An anthelmintic utilization and farm management improvement are the common prevention action, however, recently the utilization of herbs as an athelmintic has been developed, one of them is Moringa oleifera leaves. Moringa oleifera leaves are also a potential for a sources of animal food because of their high nutrients. This intervention research aimed to examine the anthelmintic effect of Moringa oleifera leaves and its potency as feed supplement. Experimental design used was ccompletely randomized design split time (CRD Split Time) with six treatments namely Moringa oleifera 5% and an infection of infective larvae of A. suum (1), Moringa oleifera 5% (2), positive control (3), Moringa oleifera 10% (4), Moringa oleifera 10% and infection of infective larvae of A. suum (5), and no treatment as negative control (6). Each treatment was imposed on four female landrace piglets aged 8 weeks and weighed around 11 kg. The results showed that Moringa oleifera 5% and 10% of the feed could inhibit the egg production of A.suum and had a significant effect (P<0.05) on weight gain of piglets. It can be concluded that Moringa oleifera leave have an anthelmintic effect to prevent the infection of A. suum and a potential for a feed supplement on pigs.
Keywords: Moringa oleifera, anthelmintic; A.suum; feed supplements; pig